CSR to tackle the Economic Effect of Covid 19:The case of Bangladesh (Bangladesh Journal of Medical Science, 2023)
Purpose – The purpose of this study is to examine the economic impact of COVID-19 and analyse how the corporate social responsibility (CSR) initiatives of Islami banks (IBs) can contribute to reducing the adverse economic impact in the context of Bangladesh.Design/Methodology/approach: Currently eight full-fledged IBs are functioning in Bangladesh adhering to the underlying principles of Shariah; among them, seven are actively engaged in CSR activities to help the underprivileged segments of its citizens. This study, through employing a content analysis method examined the information available from these IBs as well as other government sources and published materials to address the COVID-19 economic impacts, specially the role of these IBs.Findings: This study finds that along the line with national and international funds, IBs’ CSR funds can also help address the economic downturn in Bangladesh caused by the COVID-19 pandemic. The study further identified that if IBs develop a consortium among themselves, the CSR funds can be better utilised for the socio-economic development of Bangladesh.Research limitations/implications: The scope of this study is somehow limited, as it has only considered the impact of CSR funds by IBs in Bangladesh. Further research can be conducted in future considering the total CSR funds by all banks, i.e., conventional and Islamic banks.Practical implications: This study demonstrated that IBs spend USD 83.30 million annually, which means USD 417 in five years period. Based on the recommendations of this study, all IBs may work together to develop a joint CSR strategy for the socio-economic development of Bangladesh. Considering Bangladesh’s poverty level, such a joint CSR strategy would be helpful for the vulnerable population of the country.Originality/value: This study is unique in the sense that it seeks to address the economic challenges of COVID-19 in the context of Bangladesh with support from the CSR initiatives of IBs. This study has created a new insight for IBs into developing an integrated CSR strategy, which is expected to bring significant contributions to the livelihood of the susceptible citizens of this country.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 154-162